Pharmacokinetic drug evaluation of avibactam + ceftazidime for the treatment of hospital-acquired pneumonia. (4th March 2018) - Falcone, Marco; Viale, Pierluigi; Tiseo, Giusy; Pai, Manjunath
ABSTRACT: Introduction : Ceftazidime-avibactam (CAZ-AVI) is a combination of a third-generation cephalosporin and a non-β-lactam, β-lactamase inhibitor, recently approved for urinary tract infections and complicated abdominal infections. Moreover, it represents a treatment option for patients with hospital acquired pneumonia (HAP), especially when caused by multidrug-resistant (MDR) bacteria. Areas covered : The review focuses on the pharmacokinetics (PK) of CAZ-AVI in HAP and on preclinical and clinical studies evaluating PK/pharmacodynamics (PD) in this field. Expert opinion : In vitro and in vivo data about PK/PD of CAZ-AVI confirm that penetration of CAZ-AVI in the epithelial lining fluid (ELF) represents approximately 30% of the plasma concentrations. Clinical studies documented that CAZ-AVI 2000 mg/500 mg every 8 h is the optimal dose regimen to achieve the PK/PD target attainment in patients with HAP. Thus, CAZ-AVI could represent an option both to treat HAP caused by Gram-negative bacilli (GNB) displaying resistance to most of the antibiotics and to reduce the use of carbapenems, limiting the onset of resistance profiles among GNB. Additional information about specific patients populations, such as critically-ill subjects or pediatric patients, are needed for a more individualized use of CAZ-AVI.